Motivate like a CEO : communicate your strategic vision and inspire people to act! - Bates, Suzanne (New York : McGraw-Hill, 2009)
This book tells you why, then how to motivate an organisation. It is well written, clear, and motivating both for the experienced CEO and the new leader.
Includes bibliographical references (p. 269-270) and index.
aug 04/06/13
Loans
Keywords: Employee motivation; Communication in management; Strategic planning